Design of FPGA based SPWM Single Phase Inverter - Abu Bakar, Afarulrazi (2009)
Nowadays power inverter serves as an important emergency power supply system in events of mains power supply failure. The AC output voltage of a power electronic inverter is usually non-sinusoidal and hence has a high harmonic content. Sinusoidal Pulse Width Modulation (SPWM) scheme is normally used to convert the DC power supply into AC power supply by comparing the reference voltage waveform with the triangular waveform known as carrier. SPWM provides a way to reduce the total harmonic distortion of load current. The objective of this paper is to demonstrate a SPWM switching by using Altera DE2 board. In this SPWM, a sinusoidal reference voltage waveform is compared with the triangular carrier voltage to generate the on and off switching scheme. These switching schemes will trigger the gate of the power switch. In this paper, the SPWM switching strategies will be develop using Altera DE2 (Cyclone II EP2C35F672C6) with 16 bit serial configuration devices. The switching between reference and carrier waveforms of SPWM is obtained by using Matlab software. Simulation on the design pulses is conducted using Quartus II software tools provided by Altera. The output frequency of SPWM is 50 Hz and the design is limited to two levels of modulation index which are 0.5 and 0.75.